PERSEPSI PENGARANG ATAS DUNIA SOSIAL BALI - Manuaba, I. B. Putera (Diksi, 2009)
This study analyzes authors' perception of the Balinese social world, focusing onsocial changes as effects of tourism and modernization. The study employed the qualitativeapproach involving the sociology of literature, especially the sosiology of authors.Berger's social contruction theory was used as a triangulation technique. The study showsthe following findings. First, the Balinese authors subjectively propose a reconstruction ofthe modern Balinese people's way of thinking to face modernization or changingconditions. Second, the Balinese authors are ambiguous people, in the sense that on the onehand they criticize Bali, and on the other hand they love Bali. Third, the Balinese authorsoffer truths that are not dogmatic in nature but derived from daily experiences.Keywords: author plurality, social world, plurality